Development of EMG measurement system to control mobile robot using frontalis and zygomaticus major muscles - Mohamad, Ahmad Joraimee; Sidek, Shahrul Na'im; Haja Mohideen, Ahmad Jazlan; Ibrahim, Mohd Tarmizi; Ali, Kharudin (2012)
The paper discusses the development of the facial-muscle controlled robotic systems. The main work in the research is to capture the facial muscle signal activities and leverage the information to control a small mobile robot movement. The characteristic of the facial muscle activities is discussed thoroughly in this paper. The EMG measurement system is developed to condition the signal before being fed into the controller of the mobile robot system. Three channels EMG measurement systems consisting of a set of instrumentation amplifiers INA128P and four precision amplifiers OP177 are used to construct the circuit. The signal captured is amplified by 8,415 factor and filtered using bandpass filter from 50Hz to 500Hz frequency range. PIC16F877A starter kit is used to convert the analog signal into the digital form before the data is transmitted to the receiver of the mobile robot by using XBee module upon which it responds accordingly. The system is interactive and could be an exciting alternative to relieve boredom of patient doing rehabilitation exercise post stroke.